Biological warfare agents - Duraipandian Thavaselvam; Rajagopalan Vijayaraghavan (Wolters Kluwer Medknow Publications, 2010)
The recent bioterrorist attacks using anthrax spores have emphasized the need to detect and decontaminate critical facilities in the shortest possible time. There has been a remarkable progress in the detection, protection and decontamination of biological warfare agents as many instrumentation platforms and detection methodologies are developed and commissioned. Even then the threat of biological warfare agents and their use in bioterrorist attacks still remain a leading cause of global concern. Furthermore in the past decade there have been threats due to the emerging new diseases and also the re-emergence of old diseases and development of antimicrobial resistance and spread to new geographical regions. The preparedness against these agents need complete knowledge about the disease, better research and training facilities, diagnostic facilities and improved public health system. This review on the biological warfare agents will provide information on the biological warfare agents, their mode of transmission and spread and also the detection systems available to detect them. In addition the current information on the availability of commercially available and developing technologies against biological warfare agents has also been discussed. The risk that arise due to the use of these agents in warfare or bioterrorism related scenario can be mitigated with the availability of improved detection technologies.